An empirical analysis of airline business model convergence - Jost Daft; Sascha Albers (University of Cologne, Department of Business Policy and Logistics, 2014)
Based on a sample of 26 European passenger airlines, this study analyzes the development of airline business models over time. We used various distance measures to calculate concrete differentiation levels among these airlines between 2004 and 2012. The results indicate increasing similarity among these airlines, which lends support to the generally assumed convergence trend. The present paper complements the mostly qualitative and anecdotal literature on convergence in the airline industry, empirically shows actual adaptations in airlines' business models, and provides a platform for further research in the fields of empirical convergence analysis and corresponding strategic airline management.
Keywords: L10; L93; M19; 650; Airline business models; Convergence; Similarity measurement